The Sociolinguistics of Language Policy and Educational Reform in Southeast Asia - Nurhidayah, Aulia (LIER: Language Inquiry & Exploration Review, 2025)
Purpose: This study explored the impact of language policies on educational reform in Southeast Asia, focusing on Malaysia, Indonesia, and the Philippines. The findings indicate that while language policies in these countries are designed to promote national unity and global competitiveness, they often face challenges in balancing multilingualism with cultural preservation. Subjects and Methods: The study found that in Malaysia and Indonesia, the implementation of bilingual or multilingual education is hindered by resource limitations and disparities between urban and rural areas. In the Philippines, while the Mother Tongue-Based Multilingual Education (MTB-MLE) policy has shown positive results in early education, challenges remain in transitioning students to national and international languages in higher grades. Results: The study contributes to the body of knowledge by providing a comparative analysis of language policy implementation across three diverse Southeast Asian countries. It highlights the need for more inclusive and context-sensitive language policies that not only foster national unity but also preserve local languages and cultures. The findings suggest that greater attention should be given to teacher training, resource allocation, and support for multilingual classrooms. Conclusions: Future research could explore the long-term impact of language policies on students’ cognitive and socio-cultural development, as well as investigate the role of digital technology in supporting multilingual education in the region.